Ithaka S+R US Library survey 2013 - Magan-Wals, José-Antonio (Anuario ThinkEPI, 2015)
Reseña del informe: Long, Matthew P.; Schonfeld, Roger C. (2014). Ithaka S+R US Library Survey 2013. http://sr.ithaka.org/sites/default/files/reports/SR_LibraryReport_20140310_0.pdf